Maqashid Sharia and harmonizing law in Indonesia: impact for SDGs global context - Isman, Isman; Artalim Zaim, Muntaha; Baha Eldeen, Aisha (Springer, 2024)
This research delves into the Maqashid Sharia legal reasoning model and its profound impact on the indigenization of law in Indonesia, analyzed within a global context. The study explores the practical application of Maqashid Sharia principles and their influence on the adaptation and contextualization of Islamic law in Indonesia’s legal system. The research delves into various normative legal issues using a philosophical analysis in addition to interpretative and holistic methodolo gies. The findings underscore the pivotal role of the Maqashid Sharia legal reasoning model in promoting an inclusive and contextually relevant legal system that accom modates both local and global perspectives. This approach enhances the harmo nization of Islamic legal principles with changing societal norms and international standards. Moreover, it enables the preservation of cultural identity and values while adhering to the broader framework of human rights and global legal norms. Ulti mately, the research provides valuable insights for policymakers, scholars, and stake holders seeking to advance a progressive yet culturally sensitive legal framework in Indonesia and contribute to the broader discourse on the harmonization of law within a global context.